Analisis Kelayakan Investasi Penambahan Mesin Oven pada Industri Pengolahan Kayu Cv. Riau Pallet - Dewi Diniaty; Kurnia Irma Gustia Nova (UIN Sultan Syarif Kasim Riau, 2016)
CV. Riau Pallet is one private company in Pekanbaru, located on Jl. Kubang Raya Pekanbaru Panam. CV. Riau Pallet is a manufacturing company engaged in the processing of forest timber into a pallet. Pallet size produced by the company there are several types, the company usually produces pallet according to the demand of the consumer, and the type of pallet measuring 94 cm X 113 cm most into consumer demand. Judging from the development, the company has a number of concerns regarding the production of unmet consumer demand, where demand is higher than production, which resulted in the achievement of production targets by the company. It is caused by a finishing process that occurred in the engine oven. The oven is used for the drying process is still manual pallet, namely the drying process using a furnace that takes a long time, about 10-12 hours each one the drying process. This leads to not achieving the target production expected by the company. In addition the rate of disability in the process of finishing in the oven machine is very high. Additionally happened piling pallets waiting for their turn to the finishing stage. To overcome these problems, the need for the addition of a new oven at the company's engine. This study aims to analyze the feasibility of adding machine industry a new oven at the company and determine the feasibility of an investment based on technical aspects and financial aspects. From the data processing can be seen that the technical aspects of data processing made at the planning association or relationship Activity Relationship Chart (ARC) obtained Area Allocation Diagram (AAD) as the proposed layout of the room for the addition of new machines on the CV. Riau Pallet. On the financial aspect that has been done, it can be concluded that the NPV of USD 639 329 829, -, the value of MARR of 11%, IRR of 11.4%, and the value payback period or return on capital investment is for 1 year and 6 months. So that additional investment feasibility analysis on a company machine oven feasible.Keywords : investment feasibility analysis, wood processing industry, NPV, IRR, payback period